Effects of Blended Learning Approaches to Enhance Thai Language Skills for Early Childhood Caregiver Students - Prasatkaew, Sumedta; Hayeedareeyor, Nurfitthree; Rattanayium, Sanma (Al-HIKMAH Journal, 2025)
The purposes of this research were to: 1) study the learning outcomes of Thai language of students towards blended learning model 2) study the satisfaction of students towards blended learning model. The population for this study was purposively selected as 115 second-year undergraduate students in the special program, Faculty of Education, Yala Rajabhat University, who registered in the Thai language skills promotion course for early childhood, semester 1, academic year 2024. Data were collected using focus group discussion, learning outcome questionnaire, and learning management satisfaction questionnaire. Data were analyzed using descriptive statistics. The research results found that 1. The results of blended learning management on the results in promoting Thai language learning skills for early childhood children had 3 outcomes: 1. The results of Thai language learning of students on the blended learning management model. 2. The results of designing Thai language learning management with blended learning management model and 3. The results of learning management with blended learning management model for early childhood teachers/caregivers 2. The satisfaction of students towards the blended learning model towards the results in promoting Thai language learning skills for early childhood children was at the most appropriate level (M = 4.83, S.D =0.07 The results of this research can be used as basic information for blended learning management and as a guideline for developing learning management in the subject of promoting Thai language skills for early childhood children.